2017
DOI: 10.1002/jcb.26116
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA CCAT1 Promotes Glioma Tumorigenesis by Sponging miR‐181b

Abstract: Colon cancer-associated transcript 1 (CCAT1), a long non-coding RNA (lncRNA), is upregulated and has a vital role in the pathogenesis of numerous cancers. Recently, its high expression was found in glioma tissues. miR-181b is downregulated in glioma and acts as a tumor suppressor. However, the exact mechanism of CCAT1 action in the regulation of glioma development remains unknown. CCAT1 and miR-181b expression was firstly examined in glioma tissue samples by real-time PCR. An RNA interference approach was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
2

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 41 publications
2
59
0
2
Order By: Relevance
“…Emerging evidence has indicated that lncRNA could sponge miRNA and regulate the functions of miRNAs . Previous studies also indicated that MALAT1 presented various functions as miRNA sponges in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has indicated that lncRNA could sponge miRNA and regulate the functions of miRNAs . Previous studies also indicated that MALAT1 presented various functions as miRNA sponges in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Wang et al have found that DLEU1 contributes to ovarian carcinoma tumourigenesis and progression by interacting with miR‐490‐3p and altering CDK1 expression. Cui et al have reported that lncRNA CCAT1 promotes glioma tumourigenesis by sponging miR‐181b, thereby leading to derepression of its endogenous targets FGFR3 and PDGFRα; these findings point to a potential therapeutic target in glioma . A recent study verified that LINC00312 is associated with miR‐197‐3p and modulates the expression of a miR‐197‐3p target, p120, thereby providing powerful evidence that LINC00312 enhances gene expression at the post‐transcriptional level .…”
Section: Discussionmentioning
confidence: 94%
“…22 promotes glioma tumourigenesis by sponging miR-181b, thereby leading to derepression of its endogenous targets FGFR3 and PDGFRα; these findings point to a potential therapeutic target in glioma. 23,24 A recent study verified that LINC00312 is associated with miR-197-3p and modulates the expression of a miR-197-3p target, p120, thereby providing powerful evidence that LINC00312 enhances gene expression at the post-transcriptional level. 20 Here, we revealed a potential binding site within LINC00312 and miR-21 by bioinformatic prediction.…”
Section: Discussionmentioning
confidence: 97%
“…[25][26][27][28] To reveal possible binding miRNA on CCAT1, we analysed the CCAT1 sequence using miRbase (http:// www.mirbase.org/search.shtml) and identified that miR-30c-2-3p could be sponged by CCAT1 ( Figure 3A). [25][26][27][28] To reveal possible binding miRNA on CCAT1, we analysed the CCAT1 sequence using miRbase (http:// www.mirbase.org/search.shtml) and identified that miR-30c-2-3p could be sponged by CCAT1 ( Figure 3A).…”
Section: Ccat1 Acts As a Sponge Of Mir-30c-2-3p In Hcc Cellsmentioning
confidence: 99%
“…Many studies have shown that CCAT1 could function as miRNA sponge in different cancers. [25][26][27][28] To reveal possible binding miRNA on CCAT1, we analysed the CCAT1 sequence using miRbase (http:// www.mirbase.org/search.shtml) and identified that miR-30c-2-3p could be sponged by CCAT1 ( Figure 3A). Next, we could like to address whether miR-30c-2-3p could bind CCAT1 in HCC.…”
Section: Ccat1 Acts As a Sponge Of Mir-30c-2-3p In Hcc Cellsmentioning
confidence: 99%